RELATIONSHIP OF SOFT SKILLS AND EMPLOYEES PERFORMANCE OF HOTELS IN CHINA - Zhu, Qi; Syriac, Nellikunnel (INTI International University, 2023)
More and more companies realize that employees are one of the important factors for the company’s further development. If you want to develop better in the information age, you must have a group of outstanding employees. Therefore, the training plan to improve employee performance is a relatively important work in human resource management. Hard skills are just our visible professional and technical indicators, while soft skills are invisible indicators, and they are also a scale to measure a person's ability to handle things. This research aims to investigate how soft skills affect the performance of employees at Hotels in China. This study adopts convenience sampling and analyzes the data from 158 questionnaires distributed through SPSS. The analysis results will find out the more important and useful skills in Hotel. This study was conducted at the Guizhou Province, China. Three soft skills of communication, negotiation, and leadership were tested to be positively correlated with the performance of hotel employees. This research also allowed us to identify which soft skills are most important to a team to enable the overall team to succeed. This research can provide a reference for the human resource management of hotels to plan the soft skill development training of employees.